2019
DOI: 10.1108/sr-07-2019-0182
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and testing of PMOS current mirror-integrated MEMS pressure transducer

Abstract: Purpose This paper aims to describe the fabrication, packaging and testing of a resistive loaded p-channel metal-oxide-semiconductor field-effect transistor-based (MOSFET-based) current mirror-integrated pressure transducer. Design/methodology/approach Using the concept of piezoresistive effect in a MOSFET, three identical p-channel MOSFETs connected in current mirror configuration have been designed and fabricated using the standard polysilicon gate process and microelectromechanical system (MEMS) technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…Table 2 gives the various piezoresistive coefficients of p-and n-MOSFETs and it is observed that each of the π-coefficients of NMOS is having different magnitude with opposite sign as compared with that of PMOS. From literature [35][36], it has been found that the sign of overall piezoresistive coefficient (π) is negative for PMOS and positive for NMOS. Therefore, the effect of similar stress on the channel resistance and carrier mobility of pressure sensing NMOS and PMOS transistors will be opposite in nature, which is governed by Equation (5).…”
Section: Electrical Transduction Mechanism: Piezo-resistive Effect Inmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 2 gives the various piezoresistive coefficients of p-and n-MOSFETs and it is observed that each of the π-coefficients of NMOS is having different magnitude with opposite sign as compared with that of PMOS. From literature [35][36], it has been found that the sign of overall piezoresistive coefficient (π) is negative for PMOS and positive for NMOS. Therefore, the effect of similar stress on the channel resistance and carrier mobility of pressure sensing NMOS and PMOS transistors will be opposite in nature, which is governed by Equation (5).…”
Section: Electrical Transduction Mechanism: Piezo-resistive Effect Inmentioning
confidence: 99%
“…In another approach, piezo-MOS sensing, that is piezoresistive effect in MOSFET, has also found a promising application in the monolithic integration of CMOS and MEMS [19][20][21]. Piezo-MOSFETs integrated with microstructures have attracted significant interest among the researchers all over the world [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. In particular, various types of MOSFET based pressure transducers have been studied, designed and developed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation